Identifications, Cultures, and "Groupness": Reflecting on Culture from Ethnographic Research in Argentina - Balerdi, Soledad (2015)
This paper reflects on the precautions to be taken into account when addressing the study, from the point of view of the social sciences, of cultures and communities. This is done through ethnographic research in a neighbourhood (barrio) of migrants from an indigenous community in the province of Chaco, in northern Argentina, who have migrated to the city of La Plata (in Buenos Aires province) and have settled on its periphery. The article starts from the idea that ethnicity comes into play, situationally, as a resource rather than as a distinct and immutable feature. Even when it is necessary to describe how notions like culture and ethnicity act in practice and what meaning they have for the actors, social researchers should not historicize them in the specific contexts in which they are brought into play.